Decomposition of a fuzzy function by one-dimensional fuzzy multiresolution analysis / Jean-louis Akakatshi Ossako ... [et al.] - Jean-louis, Akakatshi Ossako; Rebecca, Walo Omana; Richard, Bopili Mbotia; Antoine, Kitombole Tshovu (UiTM Cawangan Perlis, 2023)
Signal compression and data compression are techniques for storing and transmitting signals using fewer bits as possible for encoding a complete signal. A good signal compression scheme requires a good signal decomposition scheme. The decomposition of the signal can be done as follows: The signal is split into a low-resolution part, described by a smaller number of samples than the original signal, and a signal difference, which describes the difference between the low-resolution signal and the real coded signal. Our paper deals with the proofs of these properties in a fuzzy environment. The proof of one- dimensional multiresolution analysis is given. The concept of fuzzy wavelets is introduced and as a byproduct a special fuzzy space of details of a signal is given and an orthonormal basis of L2(0,1,(R),, F(R)) decomposing the fuzzy signal is obtained.